Expenditure Restraint in Government Budgets in Australian Financial Management - Sampe, Stevanus (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Expenditure restraint is one of tools used by government to manage public financialresources. However, there is rationale for the prominence of expenditure restraint in governmentbudgets. This article attempts to explore the prominence of expenditure restraint and how toimplement expenditure restraint to improve economic management by focusing on expenditurerestraint in the Australian budgetary management imposed in the Fraser government (1975-1983) andin the Hawke Labor government (1983-1991), Australia.